2020
DOI: 10.1186/s13567-020-00742-8
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box 1 protein (HMGB1) from Cherry Valley duck mediates signaling pathways and antiviral activity

Abstract: High-mobility group box 1 protein (HMGB1) shows endogenous damage-associated molecular patterns (DAMPs) and is also an early warning protein that activates the body's innate immune system. Here, the full-length coding sequence of HMGB1 was cloned from the spleen of Cherry Valley duck and analyzed. We find that duck HMGB1(duHMGB1) is mostly located in the nucleus of duck embryo fibroblast (DEF) cells under normal conditions but released into the cytoplasm after lipopolysaccharide (LPS) stimulation. Knocking-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Meanwhile, NLRP3 and NLRC5 were found to be involved in DTMUV infection [82]. HMGB proteins including HMGB1 and HMGB3 have been reported to affect DTMUV replication as well [102,103]. Although various PRRs might be involved in DTMUV infection, only the expression changes of these PRRs were focused on, and their specific function needs further investigation.…”
Section: Other Prrs Relevant To Dtmuv Infectionmentioning
confidence: 99%
“…Meanwhile, NLRP3 and NLRC5 were found to be involved in DTMUV infection [82]. HMGB proteins including HMGB1 and HMGB3 have been reported to affect DTMUV replication as well [102,103]. Although various PRRs might be involved in DTMUV infection, only the expression changes of these PRRs were focused on, and their specific function needs further investigation.…”
Section: Other Prrs Relevant To Dtmuv Infectionmentioning
confidence: 99%
“…Note: The SDHZYC strain was marked with filled circles hemorrhage and necrosis in the liver. There are several notable different properties between classical MDRV and NDRV, including different antigenicity by cross-neutralization tests, host species differences, pathogenic properties, protein profiles [27][28][29], electropherotypes, and genomic coding assignments [10-13, 16, 30]. As fatal pathogenic viruses that can kill ducklings within 72 h, NDRV had caused huge economic losses for the duck industry over the past several decades [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the release of these cytokines, such as TNF-α, IL-6, and IL-1β, was induced by LPS during Escherichia coli infection ( 30 , 31 ). Further, when Cherry Valley ducks are infected with certain viruses, such as the novel duck reovirus, duck tembusu virus, and duck plague virus, these factors will be increased ( 32 , 33 ). The regulatory cytokines are also seen as being up-regulated during fungal infections ( 34 ).…”
Section: Discussionmentioning
confidence: 99%